Miedzy Polska a swiatem : kultura emigracyjna po 1939 roku - Fik, Marta; Sesja "Miedzy Polska a swiatem" (1991 : Instytut Sztuki (Polska Akademia Nauk)) (Warszawa : Wydawn. Krag, 1992)
A symposium held in 1991 on the topic of Polish emigration after 1939.
"Materialy z sesji 'Miedzy Polska a swiatem', zorganizowanej przez IS PAN w dniach 3-5 IX 1991 r."--T.p. verso.
On cover: Instytut Sztuki PAN.
Includes bibliographical references.
Keywords: Polish people -- Foreign countries -- Intellectual life -- Congresses; Poland -- Emigration and immigration -- History -- 20th century -- Congresses